Monster/beauty : building the body of love - Frueh, Joanna (University of California Press, 2001)
"This book challenges both conventional and feminist ideas about beauty by asking us to take pleasure in beauty without shame, and to see and feel the erotic in everyday life. Bringing together her varied experiences as a poet, art historian, bodybuilder, and noted performance artist, Joanna Frueh shows us how to move beyond society's equation of youth with beauty toward an aesthetic for the fully erotic human being." "A combination of autobiography, theory, photography, and poetry, this book continues to develop the ideas about the erotic, beauty, older women, sex, and pleasure that Frueh first addressed in Erotic Faculties." "Monster/Beauty examines these issues using a provocative, often explicit, set of examples. Frueh admiringly looks at the bodies and mindsets of midlife female bodybuilders, rethinks the vampire, and revises our ideas about traditional models of beauty, such as Aphrodite. Above all, she brings her personal experience into the text, weaving her reflections on female sensuality with contemporary theory." "These linked essays are as much a performance as they are a discussion, breaking down the barriers between the personal and the academic, and the erotic and the intellectual. Frueh writes passionately and beautifully, and the result is a much-needed exploration of beauty myths and taboos."--Jacket